2008
DOI: 10.1128/aem.02231-07
|View full text |Cite
|
Sign up to set email alerts
|

Population Diversity of Yeasts and Lactic Acid Bacteria in Pig Feed Fermented with Whey, Wet Wheat Distillers' Grains, or Water at Different Temperatures

Abstract: The diversity of populations of yeast and lactic acid bacteria (LAB) in pig feeds fermented at 10, 15, or 20°C was characterized by rRNA gene sequencing of isolates. The feeds consisted of a cereal grain mix blended with wet wheat distillers' grains (WWDG feed), whey (W feed), or tap water (WAT feed). Fermentation proceeded for 5 days without disturbance, followed by 14 days of daily simulated feed outtakes, in which 80% of the contents were replaced with fresh feed mixtures. In WWDG feed, Pichia galeiformis b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
59
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(63 citation statements)
references
References 35 publications
4
59
0
Order By: Relevance
“…Therefore, high concentrations of yeasts in the FLF may be beneficial. However, the yeast population was not further specified and therefore eventual beneficial or detrimental effects by the yeasts present cannot be assessed, certainly when considering the high diversity of yeasts that can be present in FLF (Olstorpe et al 2008;Gori et al 2011). Animal performances.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, high concentrations of yeasts in the FLF may be beneficial. However, the yeast population was not further specified and therefore eventual beneficial or detrimental effects by the yeasts present cannot be assessed, certainly when considering the high diversity of yeasts that can be present in FLF (Olstorpe et al 2008;Gori et al 2011). Animal performances.…”
Section: Discussionmentioning
confidence: 99%
“…Average (± SEM) villus length (V; µm), crypt depth (C; µm), villus : crypt ratio (V/C), and total length (V+C; µm) together with numbers of intra-epithelial lymphocytes per 100 enterocytes (IELs) of the small intestine at 3 m distally from stomach (SI1) and at 3 m proximally to caecum (SI2) from piglets sacrificed at 28 days post weaning of DRY and FLF fed groups in Experiments I and II (n = 9) In both of our experiments, a higher count of yeasts (P < 0.05) was noted in the gut of piglets fed FLF, compared with dry feed. As mentioned above, this high concentration of yeasts in the FLF may also be beneficial, depending on the strains present (Mul and Perry 1994;Jensen and Mikkelsen 1998;Olstorpe et al 2008;Gori et al 2011).…”
Section: Experiments IImentioning
confidence: 99%
“…In a recent study, Olstorpe et al (2008) demonstrated that the species composition in 312 fermented liquid feed may vary considerably. They showed that Pediococcus pentosaceus was 313 the dominant population at the beginning of a spontaneous fermentation, but that after 3 days of 314 continuous fermentation the Lactobacillus plantarum population had become the dominant 315 population.…”
Section: Introduction 77 78mentioning
confidence: 99%
“…Strain DBVPG 4685 from the Industrial Yeast Collection DBVPG (University of Perugia, Italy) was obtained from ascocarps of Tuber melanosporum Vitt., collected in a typical Mediterranean forest in Italy (Buzzini et al, 2005). Strain SLU J596 (5CBS 10506) from the collection of the Department of Microbiology, Swedish University of Agricultural Sciences, was isolated from a 19-day-fermented mixture of cereal grains, collected east of Uppsala Olstorpe et al, 2008). Four of the isolates included in this work were not obtained by the authors of this paper and data on these strains were kindly provided by the respective investigators.…”
Section: Strainsmentioning
confidence: 99%